Edukasi Manfaat Adanya Perusahaan Asuransi di Kalangan Mahasiswa UIN KHAS Jember - Musfiroh, Luluk; Ferawati, Yuda; Azizatussa'adah, Nurul (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2024)
Insurance Company is a company that provides risk coverage services due to loss, damage etc. In Indonesia, which has a dense human population and a high level of accident risk, of course education about the benefits of insurance companies is very important, especially among students who are agents of change. Therefore community service activities in the form of socializing the benefits of having an insurance company are carried out targeting UIN KHAS Jember students. This community service activity was carried out on May 23, 2023 to be precise in the Sharia Accounting 3 semester 6 class of UIN KHAS Jember. The method used in this service uses case studies and presentations in class. The purpose of this service is for UIN KHAS Jember students to know the benefits of having an insurance company in the community.